Vulvar cicatricial pemphigoid in a child - (:unkn) unknown (My University, 1994)
Cicatricial pemphigoid is a rare disease primarily affecting the elderly. Only a few cases of childhood cicatricial pemphigoid have been reported in the literature. We present a case of cicatricial pemphigoid involving the vulvar region in a child. Copyright © 1994, Wiley Blackwell. All rights reserved
Keywords: Childhood; Cieatricial pemphigoid; Vulvar